Knowledge Regarding Brain Death and Organ Donation Laws Among Medical Students. (July 2018) - Balwani, Manish; Pasari, Amit; Aziz, Feroz; Patel, Mohan; Kute, Vivek; Shah, Pankaj; Gumber, Manoj
Abstract : Background: To determine the knowledge regarding brain death and organ donation laws among medical students. Methods: The study was carried out at Jawaharlal Nehru Medical college, Sawangi, Maharashtra, India. MBBS students took part in the study. A questionnaire was distributed among participants where they were asked to tick the appropriate answer in response to the questions. Data entry was made in excel software in codes and analysis was done by SPSS software. Results: About 300 participants participated in the study. All were aware of the term organ donation but knowledge about its various aspects was low. About 80% students were aware of green corridor, most of them (62%) first heard it through print media. Around 90% said that there is difference between donation after brain death and cardiac death. Only 30% could correctly tick all possible organs which can be donated after brain death. Around 15% answered correct sequence of abdominal organ procurement in a brain dead person. About 40% were aware of national organ donation law. Around 70% participants were of opinion that our organ allocation system is transparent enough. Only 2 % participants had pledged prior to study to be an organ donor. About 90% students had no idea about the point of intact in case of cadaver identification. Around 90% said that their religion allows for organ donation. Around 30% answered correctly about the contraindications of organ donation in a brain dead person. Conclusion: Better knowledge and awareness about brain death and organ donation laws will help in early identification of cadaver. A thorough topic should be covered in MBBS syllabus with in hand practical involvement of students while carrying out organ donation and allocation activities. This will help in removing fears and hesitancy among medical fraternity regarding organ donation.